Reverse koebner phenomenon in bullous pemphigoid - A case report - Liza Mohapatra; Kallolinee Samal; Prasenjeet Mohanty; Siddhartha Dash (Wolters Kluwer Medknow Publications, 2019)
Reverse Koebner response is the nonappearance or disappearance of the lesions of particular dermatoses at the site of injury. Herein we report a case of the reverse Koebner phenomenon in bullous pemphigoid in a 35-year-old male patient with sparing of the waist area which could probably be because of the phenomenon of locus majoris resistentiae. The histopathology of the lesion showed subepidermal split with a mixed inflammatory infiltrate, which was composed of predominantly eosinophils, neutrophils, and lymphocytes, but the histopathology of the spared skin showed no abnormalities. However, the direct immunofluorescence from the perilesional area showed linear deposits of immunoglobulin G and C3 in the dermoepidermal junction, but there were no deposits in direct immunofluorescence from the spared skin. This case is being reported for its originality and one of its kind.